Friendship and peer culture in multilingual settings - Theobald, Maryanne (Bingley : Emerald Group Publishing Limited, 2016)
Authors of this book discover the intricacies of friendship and peer cultures of children in multilingual settings. Volume 21 brings together empirical research from across the globe, and from various methodological and theoretical orientations to investigate childrens relationships within multilingual settings such as school, home, community and online. Diverse views of children and young people on cross-cultural relationships offer rich and valuable findings and contribute new knowledge for policy makers, social workers, educators and parents about strategies children use to make friends.Internationally, the linguistic diversity of communities in the minority world is at its highest to date. With increasing numbers of children learning a language other than their home language at school or other places, it is important to understand the nature of the social relationships that children and youth are experiencing in their everyday lives in order to improve their chances of successful social experiences in the future. Applying a sociological perspective, this volume features the rich, varied and complex aspects of children's experiences of friendship in multilingual settings.
Prelims -- Friendship, participation, and multimodality in Moroccan immigrant girls peer groups -- Speaking distance: language, friendship and spaces of belonging in irish primary schools -- Fiji school students multilingual language choices when talking with friends -- Language, identity and peer interactions at a linguistically diverse school -- The dilemma of deviant subcultures for immigrant youth integration: an analysis of popularity attainment in Israeli schools -- Peer collaboration in front of two alphabet charts -- "I'm your best friend": peer interaction and friendship in a multilingual preschool -- Multiple involvements in interactional repair: using smartphones in peer culture to augment lingua franca English -- Intercultural learning and friendship development in short-term intercultural education programmes -- Whanaungatanga relationships: within a one day school of te reo maori excellence -- About the authors.
Includes bibliographical references.
Print version record
Keywords: Social Science -- Children's Studies; Age groups: children; Friendship in adolescence; Multiculturalism